The Degree of Application the Principles of Knowledge Economy at Taibah University from the Perspective of Faculty Members - Majed Alzyoudi; Mohammad Jouhani (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: The study aimed to identify the degree of application of the principles of Knowledge Economy at Taibah University from the perspective of the faculty members. Methods: To achieve this, the researcher used the descriptive survey approach. The study sample consisted of (122) faculty members from Taibah University in the College of Education and the College of Science. The researchers prepared a questionnaire to measure the principles of Knowledge Economy at Taibah University in the following domains: research, innovation, ICT implementing and governance. Validity and reliability of the study tool was verified. Results: The study showed that the degree of applying the principles of Knowledge Economy medium. Employing ICT was large, followed by governance, and the principle of research and innovation with a medium degree. The results revealed statistically significant differences in the degree of application of Knowledge Economy Principles due to the faculty variable in all fields in favor of education faculties, and there were statistically significant differences in the degree of application of Knowledge Economy Principles due to the academic rank variable. And there were differences in the ICT employment, in favor of the rank of associate professor. However, the results showed that there were no statistically significant differences in the degree of application of knowledge economy principles in general, due to the experience variable. Conclusion: The need for a comprehensive revision for applying the Principles of Knowledge Economy in the University to identify the factors that lowered these results.